Does Mineralocorticoid Receptor Antagonism Prevent Calcineurin Inhibitor-Induced Nephrotoxicity? - Mortensen, Line Aas; Bistrup, Claus; Thiesson, Helle Charlotte (Frontiers in Medicine, 2017)
Calcineurin inhibitors have markedly reduced acute rejection rates in renal transplantation, thus significantly improved short-term outcome. The beneficial effects are, however, tampered by acute and chronic nephrotoxicity leading to interstitial fibrosis and tubular atrophy, which impairs long-term allograft survival. The mineralocorticoid hormone aldosterone induces fibrosis in numerous organs, including the kidney. Evidence from animal models suggests a beneficial effect of aldosterone antagonism in reducing calcineurin inhibitor-induced nephrotoxicity. This review summarizes current evidence of mineralocorticoid receptor antagonism in animal models of calcineurin inhibitor-induced nephrotoxicity and the results from studies of mineralocorticoid antagonism in renal transplant patients.